2022
DOI: 10.5395/rde.2022.47.e7
|View full text |Cite
|
Sign up to set email alerts
|

In-office dental bleaching with violet light emitting diode: bleaching efficacy and pulpal temperature rise

Abstract: Objectives This study evaluated the bleaching efficacy of different in-office protocols associated with violet light emitting diode (V-LED), and measured the pulpal temperature rise caused by V-LED with or without gel application. Materials and Methods Bovine incisors were distributed in 4 groups ( n = 10): VL – V-LED; HP – 35% hydrogen peroxide (control); HYB – hybrid protocol, V-LED applied without gel for 10 irradiation cycles followed by V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…46 Additionally, some research has demonstrated that light-activated bleaching worsens tooth sensitivity by heating the tooth and releasing more free radicals into the pulp. 47,48 Other in vitro studies showed that applying bleaching gel along with halogen light caused the cultured odontoblast to experience more severe cytotoxic effects than applying hydrogen peroxide alone. 49 Conversely, another study found no proof that light activation during in-office bleaching influenced the risk and severity of TS, regardless of hydrogen peroxide concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Additionally, some research has demonstrated that light-activated bleaching worsens tooth sensitivity by heating the tooth and releasing more free radicals into the pulp. 47,48 Other in vitro studies showed that applying bleaching gel along with halogen light caused the cultured odontoblast to experience more severe cytotoxic effects than applying hydrogen peroxide alone. 49 Conversely, another study found no proof that light activation during in-office bleaching influenced the risk and severity of TS, regardless of hydrogen peroxide concentration.…”
Section: Resultsmentioning
confidence: 99%
“…However, another study revealed that when light activation was used, tooth sensitivity increased 24 h after bleaching 46 . Additionally, some research has demonstrated that light‐activated bleaching worsens tooth sensitivity by heating the tooth and releasing more free radicals into the pulp 47,48 . Other in vitro studies showed that applying bleaching gel along with halogen light caused the cultured odontoblast to experience more severe cytotoxic effects than applying hydrogen peroxide alone 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a noninvasive mode for treating many medical conditions such as tumours and skin problems (12,13) . Photodynamic bleaching of teeth was reported to be effective when photosensitizing agents (such as rhodamine-B) are added to peroxide bleaching material (14)(15)(16)(17)(18) . Low-intensity visible light source activates peroxide oxidation and enhances the breakdown rate of Reactive Oxygen species (ROS) speeding up the bleaching procedure (18) .…”
Section: Introductionmentioning
confidence: 99%
“…Among these, In-office or power bleaching is done under the close observation of a clinician to prevent damage to soft tissues and gel ingestion. This shortens the overall treatment duration and results in a quicker turnaround in terms of bleaching efficacy [6]. The most commonly used In-office or Power bleaching techniques use hydrogen peroxides with high concentrations and are frequently referred to as "one-hour bleaching."…”
Section: Introductionmentioning
confidence: 99%